EXPLORASI KOMUNIKASI DAN EDUKASI MUSIK DI INSTAGRAM: STUDI ETNOGRAFI VIRTUAL @SCWXYZ KEPADA GITARIS PEMULA - Giardana, Tegar Gilang; Mubarok, Muhamad Husni (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2025)
The use of Instagram has become progressively more adaptive and transformative, especially in facilitating the creation and distribution of music-related content. The Instagram account @scwxyz plays an active role in sharing musical knowledge, particularly for novice guitarists. This account facilitates interaction and informal learning among its followers. The purpose of this study is to analyze the communication patterns between the account owner of @scwxyz and their followers, explore the followers’ learning experiences, and examine the accuracy and appropriateness of the musical knowledge presented. Employing a qualitative approach, this research adopts virtual ethnography as its method, collecting data through observation, in-depth interviews, and documentation. The findings of media space reveal that the platform functions as a comprehensive, guitar-oriented space that stands apart from traditional, course-based learning models. At the document media level, a variety of interactions and informal learning take place through text, images, and video content. The object media level indicates active user engagement and direct communication with the account owner. Lastly, at the media experience level, followers express their motivations, perceived benefits, and the sense of reciprocal interaction they experience. Overall, the communication pattern on @scwxyz is two-way, enabling followers to ask questions, receive feedback, and engage in hands-on guitar practice on Instagram.